Changes in Wage Distributions, Wage Gaps and Wage Inequality by Gender in Kenya - Agesa, Richard U.; Agesa, Jacqueline; Dabalen, Andrew (2012)
Using data from Kenya, the determinants of gender differences in the overall distribution of earnings are estimated as part of explaining the positive association between the return to measured and unmeasured human capital attributes as formalised by human capital theory (Mincer in 'Schooling Experience, and Earnings', New York: National Bureau of Economic Research, Columbia University Press, 1974). The Kenyan data allows us to demonstrate that males possess relatively more human capital, and once gender differences in measured and unmeasured skills are accounted for, males receive relatively higher returns to both their measured and unmeasured human capital attributes. These findings support the notion that gender differences in the return to human capital trigger male and female earnings differences in Kenya.